2012
DOI: 10.1093/czoolo/58.6.820
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive traits of the gray ratsnake Ptyas korros from three geographically distinct populations

Abstract: We collected gravid gray rat snakes Ptyas korros from three geographically distinct populations in China, Chenzhou (CZ), Jiangshan (JS) and Dinghai (DH), to study geographical variation in female reproductive traits. Egg-laying dates differed among the three populations such that at the most northern latitude egg-laying was latest, and earliest at the most southern latitutde. Clutch size, clutch mass, egg mass, egg shape, within clutch variability in egg sizes and relative clutch mass differed among the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…We did not detect the egg size number trade-off in L. rufozonatum . This affirms the results reported for three colubrid snakes of the genus Ptyas , P. mucosus [ 53 ], P. korros [ 54 ], and P. dhumnades [ 29 ], where females do not trade off egg size against number. By contrast, the egg size number trade-off is significant in the king ratsnake Elaphe carinata [ 42 ] and the Chinese cobra Naja atra [ 37 ] but, in both species, there is a fixed upper limit (~1.4 times greater that the population mean egg size) to egg size not set by the maternal body volume [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…We did not detect the egg size number trade-off in L. rufozonatum . This affirms the results reported for three colubrid snakes of the genus Ptyas , P. mucosus [ 53 ], P. korros [ 54 ], and P. dhumnades [ 29 ], where females do not trade off egg size against number. By contrast, the egg size number trade-off is significant in the king ratsnake Elaphe carinata [ 42 ] and the Chinese cobra Naja atra [ 37 ] but, in both species, there is a fixed upper limit (~1.4 times greater that the population mean egg size) to egg size not set by the maternal body volume [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…As a result of the lower ambient temperatures, embryos in high latitudes or altitudes grow at a slower rate than those at lower latitudes or altitudes ( Mathies and Andrews 1995 ), and our results follow this rule. On the other hand, at lower altitudes, the date of emergence from hibernation is earlier for reptiles, and the time between emergence and ovulation can influence their egg-laying or parturition dates ( Ji and Wang 2005 ; Lin et al 2012 ). In this study, we also noticed that low-altitude lizards emerged from hibernation around mid-April, while high-altitude lizards emerged around mid-May, which is consistent with the above situation.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation revealed that the female of S. chinensis oviposits at mid-June and hatched out at the end of July (i.e., summer season). Marques and Pizzatto (2002), Lin et al (2012), and SantoshKumar and Kannan (2016) have reported similar patterns of egg laying and hatching of Oxyrhopus guibei, P. korros, and Xylophis perroteti, respectively. This captive egg laying in summer might be the result of two mating seasons (i.e., autumn and spring).…”
Section: Resultsmentioning
confidence: 83%